Digital Supervision and Team Work of Science Education at Vocational School - Saut Purba; Abdul Hasan; Keysar Panjaitan; Binsar Maruli (Jurnal Penelitian Pendidikan IPA, 2023)
The advances of information technology affect the variety of learning materials. This reality must be responded by developing learning model and also supervision system. The supervision and team work at science education also can be coordinated with the development of technology, especially technology based on handheld devices such as such as phones and tablets. This research aims to describe and determine: The influence of academic supervision on teamwork; The Effect of Academic Supervision on Teacher Job Satisfaction; The Effect of Teamwork on Job Satisfaction of State Vocational School Teachers in Medan City. The research method used is a quantitative method with a survey approach. The number of respondents was 198 people taken using Proportional Random Sampling techniques. The research instrument is a questionnaire, which is first tested to obtain a valid and reliable instrument. The result of this research shown that the digital supervision can be make the system more and more efficiently. This context of research academic Supervision has a direct positive effect on Teamwork of State Vocational Teachers in Medan City. In other words, the better the Academic Supervision, the better the Teamwork of State Vocational Teachers in Medan City, Academic Supervision has a direct positive effect on the Job Satisfaction of teachers of public vocational schools in Medan City. In other words, the better the Academic Supervision, the higher the Job Satisfaction of State Vocational Teachers